Implementation Of Artificial Intelligence In Innovation Of Modern Engineering And Industrial Systems - Hanif Megantoro; Siska Aprelyani (Greenation Research & Yayasan Global Resarch National, 2025)
Literature Review on the role of Artificial Intelligence (AI) as a factor influencing the efficiency, performance, and innovation of modern industrial systems is a scientific article with the objective of analyzing whether the implementation of Artificial Intelligence (AI) plays a role in improving industrial system efficiency and performance, as well as in driving process and product innovation within the context of Industry 4.0 and Industry 5.0. This research method using document analysis by examining relevant national and international journal articles, conference proceedings, and reference books related to artificial intelligence, industrial automation, predictive maintenance, supply chain management, and industrial innovation. The results of this article indicate that: 1) the implementation of Artificial Intelligence (AI) significantly influences the efficiency and performance of modern industrial systems, particularly through production automation, predictive maintenance, and real-time data analysis; 2) the adoption of Artificial Intelligence (AI) contributes positively to innovation in industrial processes and products, enhances system adaptability, and supports data-driven decision-making in contemporary industrial environments. In addition to AI implementation, industrial efficiency and innovation are also influenced by other factors, including digital infrastructure readiness, workforce competencies, organizational strategy, data governance, and technological integration capabilities.